Pengaruh model cooperative learning tipe jigsaw dengan media diorama terhadap hasil belajar IPS materi kebudayaan daerah siswa kelas 4 sekolah dasar - Puspitasari, Aisyah; Poerwanti, Jenny Indrastoeti Siti (Universitas Sebelas Maret, 2026)
this study set out to ascertain the extent to which the Jigsaw Cooperative Learning model, with the use of diorama, influenced the social studies learning outcomes pertaining to local studies including local materials studied by four fourth-grade elementary school students. This research is classified as quantitative since it uses a pretest-posttest control group design and a quasi-experimental methodology. The sample was selected using the cluster random sampling approach and subsequently split into experimental and control groups. In this study, a learning outcome test is used to collect data, which is subsequently analyzed using Mann Whitney. The result showed that student with Jigsaw cooperative learning model had better learning outcomes than student whit team tournament model. The control group received an average score of 75, whereas the experimental group received an average score of 85. The results of hypothesis testing indicate that the use of diorama media in conjunction with the Jigsaw cooperative learning paradigm significantly affects social studies learning outcomes for local cultural information. A significance level of 0.05 is used in this investigation.